JAK2, CALR, and MPL Mutation Profiles in BCR-ABL Negative Myeloproliferative Neoplasms, a Referral Center Experience in the Middle East - Moeinadin Safavi; Ahmad Monabati; Akbar Safaie; Maryam Mirtalebi; Masoumeh Faghih (Iranian Society of Pathology, 2021)
Background: This study was conducted to evaluate the frequency of JAK2, CALR and MPL mutations in with BCR-ABL myeloproliferative neoplasms and their association with demographic data and hematologic parameters in a referral center, in the Middle East. Methods: Seventy-one patients with BCR-ABL negative myeloproliferative neoplasms were evaluated for JAK2 V617F, CALR type 1, type 2, and MPL by allele-specific PCR and conventional PCR from 2018 to 2019. Results:  Twenty three patients were categorized as polycythemia vera and demonstrated JAK2 V617F in 91.3 % of these cases. Thirty-eight patients were classified as essential thrombocythemia and showed JAK2 V617F in 52.6%, CALR type 1 in 18.4%, CALR type 2 in 7.9% and no mutation in 21.1%. Seven patients were recognized as primary myelofibrosis and exhibited JAK2 V617F mutation in 57.1%, CALR type 1 in 14.3 %, CALR type 2 in 14.3% and no mutation in 14.3%. Three patients were diagnosed as MPN, unclassifiable and revealed JAK2 V617F mutation in 33.3% and no mutation in 66.6%.The age (59.15±13.10) and neutrophil percent (70.78±10.14) were higher in patients with JAK2 mutation compared to other mutations (p=0.000, and p=0.03). Platelet count was significantly higher in patients with CALR type 1 mutation (1240400± 402053) (p=0.000). Conclusion: JAK2 V617F was was associated with patients' higher age and higher neutrophil count in CBC. CALR mutation had an association with higher platelet count. No MPL mutation was found in this study and it seems that its frequency is lower than what is expected in this region.